Common dysfunctional variants in ABCG2 are a major cause of early-onset gout - Matsuo, Hirotaka (Nature Publishing Group, 2013)
Gout is a common disease which mostly occurs after middle age, but more people nowadays develop it before the age of thirty. We investigated whether common dysfunction of ABCG2, a high-capacity urate transporter which regulates serum uric acid levels, causes early-onset gout. 705 Japanese male gout cases with onset age data and 1,887 male controls were genotyped, and the ABCG2 functions which are estimated by its genotype combination were determined. The onset age was 6.5 years earlier with severe ABCG2 dysfunction than with normal ABCG2 function (P = 6.14 × 10(−3)). Patients with mild to severe ABCG2 dysfunction accounted for 88.2% of early-onset cases (twenties or younger). Severe ABCG2 dysfunction particularly increased the risk of early-onset gout (odds ratio 22.2, P = 4.66 × 10(−6)). Our finding that common dysfunction of ABCG2 is a major cause of early-onset gout will serve to improve earlier prevention and therapy for high-risk individuals.